International cooperation : the extents and limits of multilateralism - Zartman, I. William; Touval, Saadia (Cambridge : Cambridge University Press, 2010)
A number of new approaches to the subject of international cooperation were developed in the 1980s. As a result, further questions have arisen, particularly with regard to the methods and limits of cooperation and the relationship between cooperation and the debate over multilateralism. International Cooperation considers these questions, identifies further areas for research, and pushes the analysis of this fundamental concept in international relations in new directions. Its two parts address the historic roots and modern development of the notion of cooperation, and the strategies used to achieve it, with a conclusion that reaches beyond international relations into new disciplinary avenues. This edited collection incorporates historical research, social and economic analysis and political and evolutionary game theory.--From publisher description.
Introduction: return to the theories of cooperation / William Zartman and Saadia Touval -- Debating cooperation in Europe from Grotius to Adam Smith / Alexis Keller -- The two sides of multilateral cooperation / Charles Doran -- Deconstructing multilateral cooperation / Fen Osler Hampson -- Negotiated cooperation and its alternatives / Saadia Touval -- Synthesizing rationalist and constructivist perspectives on negotiated cooperation / P. Terrence Hopmann -- The shadow of the past over conflict and cooperation / Allison Stanger -- Chicken dilemmas: crossing the road to cooperation / Joshua S. Goldstein -- Conflict management as cooperation / I. William Zartman -- Status concerns and multilateral cooperation / Deborah Welch Larson and Alexei Shevchenko -- Assymetrical cooperation in economic assistance / Jean-Claude Berthelemy -- Conclusion: improving knowledge of cooperation / Saadia Touval and I. William Zartman.
Includes bibliographical references (p. 238-265) and index.
Keywords: International cooperation